Keberkesanan kaedah pengajaran perbandingan konsep dalam pembelajaran konsep sejarah bagi pelajar tingkatan empat - Lai, Geok Hiong (2011)
This study aimed to analysis the level of acceptance of Form 4 students in two schools (school A and B) on the learning of history by using two different approaches, namely the comparative concept teaching method and the conventional lecture method. This study also aimed to analysis the effectiveness of the two aforementioned teaching methods in Form 4 students' achievement in history in school A and B. The study was conducted in two secondary schools in Sibu Division. This study used a quasi experimental design, which was implemented using pre-test, post-test and questionnaire. The researcher translated and modified the questionnaire originally used by Teo (2006) to meet the needs of this study. This research involved a total of 63 respondents, which was comprised of 30 males and 33 females. The teaching and learning sessions by using the comparative concept teaching method and the conventional lecture method lasted for 11 weeks. The data collected were analyzed by using the Statistical Package for Social Science (SPSS) version 14.0. Descriptive analysis techniques such as mean score and standard deviation were used to analysis the respondents' level of acceptance regarding the comparative concept teaching method. The overall finding of the study indicated that the mean score of the level of acceptance (M = 5.66) of students in school A is higher than that in school B (M = 5.3). Also, the study showed that the passing rate of he Form 4 students in school A (pre-test: 72.22%, post-test 1: 86.11%, post-test 2: 94.44%, post-test 3: 97.22%, post-test 4: 100% and post-test: 100%) was higher than that in school B (pre-test: 55.55% , post-test 1: 59.26%, post-test 2: 66.67%, post-test 3: 70.37%, pst-test 4: 71.77% and post-test: 81.48%). This study showed that the comparative concept teaching method was effective in the teaching and learning of history and hence, it can be employed in the instructional process to make history an interesting and likeable subject